Uso de diferentes revestimentos na produção de pré-secado de gramíneas tropicais - Silva, Alex Lopes da (2020)
Two experiments were carried out with haylage, one with marandu grass and the other with tanzania grass, both with the same objective, which consisted of evaluating the gas quantification, temperature, fermentation characteristics, chemical composition and aerobic stability of the haylage coated with films of different thicknesses. Four plastic films of different thicknesses were tested as haylage coating (10, 11, 13 and 27µm) associated to storage times and during aerobic stability (0, 48 and 96 h) in a completely randomized design with three replications organized in factorial schemes. Gas quantification and temperature were evaluated in the first 48 h (4 × 4), being four films and four storage times (0, 12, 24 and 48 h) and over the storage days (4 × 5), four films and five storage times (0, 7, 15, 30 and 60 d). The fermentative characteristics were evaluated in a factorial scheme (4 × 4), being four films and four storage times (7, 15, 30 and 60 d). In the evaluations during aerobic stability (4 × 3), there were four films and three storage times (0, 48 and 96 h). The chemical composition was evaluated only after the opening at 60 days. In the marandu grass, the oxygen concentration stabilized at 12 h below 5% and the carbon dioxide after 7 d with 37.17%. There was little variation in pH, and the lowest values were observed at 60 days (pH 5.13 to 5.4). There was a predominance of molds and yeasts with little variation between the films (7.02 to 7.51 log10 cfu g -1 ), as well as lactic acid bacteria (5.54 to 6.11 log10 cfu g-1 ) and enterobacteria (6.34 to 6.84 log10 cfu g-1 ). There was effect only on the dry matter, with the highest average in the treatment of 13µm (522.4 g kg-1 DM). In the Tanzania grass, the O2 concentration stabilized at 12 h below 4%. The highest pH was in the 27 µm film at 7 and 15 days (pH 7.15 and 6.54, respectively), whereas at 60 days, all films had a similar pH. Higher averages of molds and yeasts were observed in the film of 27µm (7.13 log10 cfu g-1 ) and 13µm (7.32 log10 cfu g-1 ) in the effect of the film. The film of 13µm provided a higher content of dry matter (655 g kg -1 ) and crude protein (140.9 g kg-1 DM). In both experiments, all coatings allowed low fermentation of organic acids and low ammoniacal nitrogen concentration, as well as a stable temperature during the aerobic stability of 96 h. Thus, films of 10, 11, 13 and 27µm of thickness can be used in the coating of haylage of marandu and tanzania grass. The use is recommended after 60 days of storage.